STUDI ISLAM: METODE TAHFIDZ AL-QUR’AN DI KOMPLEK BEYT TAHFIDZ AN-NIFISAH (BETA) ALI MAKSUM KRAPYAK - Nasrun, Abdul Qawwiy; Hanuna, Iffah Mirrotin (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2022)
Many tahfidz Al-Qur'an huts have better quality than Beta huts. In addition, a santri needs other activities besides memorizing the Qur'an to support their future life. This paper will thoroughly explain the method and other activities that exist through the results of the research. In this paper at least the author will discuss 1). What are the methods of the Tahfidzul Al-Qur'an Program at this Beta cottage? 2). Are there activities other than the Tahfidz Al-Qur'an Program at this Beta cottage?. In the results of the study, the authors conclude that there are several methods of tahfidz Al-Qur'an applied by Pondok Beta, the first is ziyadah, second, muroja'ah, third, tahsin qira'at and the fourth is sema'an. Not only the method, in this Beta cottage, the students are also given charitable advice to keep their memorization from being lost or forgotten, namely by performing tahajjud prayers and voluntary fasting. Then in this beta cottage also has other activities besides memorizing the Qur'an, namely sorogan scriptures, angklung art, bandongan, tambourines, speech exercises and English exercises. Key words : 1) pondok pesantren, 2) tahfidz, 3) method, 4) ziyadah, 5) muroja’ah, 6) tahsinul qira’at, 7) sema’an